Azure functions : getting started - Malik, Sahil (Apress, 2018)
"Azure Functions is central to Microsoft's serverless computing offering for the cloud. It is an event-driven, compute-on-demand experience that extends the existing Azure application platform with capabilities to implement code triggered by events occurring in Azure or third-party services, as well as on-premises systems. Who this video is for: NodeJS or C# developers."--Resource description page